A Review of Endometriosis: Focus on its Pathophysiology, Quality of Oocyte and Embryo, and the Management of Infertility - Yuningsih, Tita; Bustami, Arleni (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Endometriosis is a chronic inflammatory disease characterized by the presence of endometrial tissue/lesion outside of the uterus. Unveiling pathogenesis and pathophysiology of the disease remains an elusive target to be discovered. Among many other mechanistic theories, menstrual retrograde theory is favorable in explaining endometriosis which corroborated with certain survival factors that allow endometrial cells to grow and persist. This review set out to provide an update on oocyte and embryo quality derived from women with endometriosis who undergo IVF cycles. Database searching was conducted using PUBMED and the keyword used for literature searching was endometriosis, oocyte quality, and embryo quality. As a chronic inflammation occurs in reproductive tract, endometriosis has been demonstrated to negatively impact the oocyte quality and endometrial receptivity that leads to infertility. Account for about 10-40% of women with endometriosis administered in-vitro fertilization (IVF) programs to achieve pregnancy and healthy live-birth babies. Through IVF, oocytes can be fertilized and cultured in-vitro; thus, avoiding pra-implantation embryos to grow under unfavorable in-vivo tubal and endometrium environments due to endometriosis. IVF could be a method of choice for infertility treatment owing to endometriosis. Improved quality of oocyte, embryo as well as clinical pregnancy could be attained depending on endometriosis severity.